Like, Share and Comment. The Use of Facebook by Public Libraries and Museums: A Case Study from Tromsø, Norway - Skare, Roswitha (De Gruyter Saur, 2020)
Historically, libraries, archives and museums (LAMs) have been perceived as institutions providing infrastructure for an open and enlightened public discourse. While Norwegian public libraries are regulated by law that focuses on libraries being providers of knowledge and agents of popular enlightenment as well as local meeting places and arenas for debate,¹ the Norwegian museum sector is governed by relatively general and open political signals about the role of museums in society. Nevertheless, diversity, inclusion, and dialogue are important key words for both institutions.² In addition, public libraries and museums are also supposed to keep up with technological development, not only to digitize their own collections but also to offer digital services to the public.³ Most public libraries and museums do not only have official webpages offering information about their services and self-services, but are also present on social media platforms like Facebook, Twitter, Instagram or YouTube. This article investigates how three institutions in Tromsø (the main branch of the Tromsø public library and two museums) are using Facebook. By analyzing the frequency of posts, their content and the user participation created, I seek to answer the following questions: what type of posts are the institutions posting? What type of posts are the ones that engage users? What type of user engagement is most common? What similarities and differences can be observed between the three institutions? By answering these questions, I hope to show how the three institutions and their followers use Facebook. I have chosen to focus on the institutions’ Facebook pages because Facebook is by far the most popular social media platform with about 64% of the Norwegian population having a Facebook account in 2017. All three institutions are in addition to Facebook also present on other social media platforms like Instagram, Twitter or Flickr, but the highest number of followers is on Facebook.